Outbreak of type C botulism in chickens in Pancas city, Espírito Santo state, Brazil Surto de botulismo tipo C em frangos na cidade de Pancas, Espírito Santo, Brasil - Rodrigo Otávio Silveira Silva; Prhiscylla Sadanã Pires; Felipe Masiero Salvarani; Carlos Augusto de Oliveira Júnior; Gustavo Xavier Wassita de Souza; Fernanda Celano de Minas Santos; Rogério Pinheiro Caldas; Ronnie Antunes de Assis; Francisco Carlos Faria Lobato; Guilherme Guerra Alves (Semina: Ciências Agrárias, 2013)
This work aims to describe an outbreak of botulism in poultry (Gallus gallus domesticus), in Pancas City, Espírito Santo State, Brazil. The birds were derived from a subsistence property with approximately 150 domestic fowls. The owner reported finding some birds lying on the floor and others exhibiting limited mobility. Ten animals in agony were euthanized, necropsied and had their blood serum collected. About 72 hours after the onset of clinical signs, 144 (96%) animals of the creation had already died. No postmortem changes were found at necropsies. Clostridium botulinum type C toxins were detected in the sera of euthanized chickens by mice neutralization tests. The observation of clinical signs, absence of post-mortem lesions and the result of mouse neutralization tests confirmed the diagnosis of botulism caused by C. botulinum type C. Unfortunately, the source of toxins was not found. O presente trabalho tem como objetivo descrever um surto de botulismo em aves domésticas (Gallus gallus domesticus), ocorrido na cidade de Pancas, estado do Espírito Santo, Brasil. As aves eram oriundas de uma propriedade de subsistência com aproximadamente 150 frangos domésticos. O proprietário relatou encontrar algumas aves caídas no chão e outras apresentando dificuldade de locomoção. Dez animais em estado agônico foram eutanasiados, submetidos à necropsia e coleta de soro sanguíneo. Em 72 horas após o início dos sinais clínicos, 144 (96%) animais da criação já haviam vindo a óbito. Nenhuma alteração post-mortem foi encontrada durante a necropsia. Foi possível detectar a toxina botulínica tipo C por soroneutralização em camundongos no soro dos animais eutanasiados. A observação da sintomatologia clínica, ausência de lesões à necropsia e o resultado da soroneutralização permitem confirmar o diagnóstico de botulismo por Clostridium botulinum tipo C.